2001
DOI: 10.1021/ef010047l
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Precipitation from Live Crude Oil

Abstract: Asphaltene precipitation from live crude oils that occurs due to pressure reduction can foul and clog oil production equipment, at the well surface, in the borehole, and even in the subsurface formation, thus is of considerable interest to oil operating companies. We employ near-infrared (NIR) spectroscopy to characterize this asphaltene precipitation process; in particular, the independent measurements on asphaltene flocculation of wavelength dependence of optical scattering and of sedimentation rates are per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 19 publications
(47 reference statements)
5
111
0
Order By: Relevance
“…The asphaltene fraction is composed of the heaviest components in crude oils. Separated solid asphaltenes usually appear brown to black and have no definite melting point but decompose when the temperature exceeds 300-400 o C. It has been shown that changes in temperature [24,25], pressure [26][27][28] and oil composition [29] can cause asphaltene precipitation. Asphaltenes are flat sheets of condensed polyaromatic hydrocarbons interconnected with sulfide, ether, aliphatic chain, and naphthenic ring linkages [30,31].…”
Section: Surface-active Species In Crude Oilmentioning
confidence: 99%
“…The asphaltene fraction is composed of the heaviest components in crude oils. Separated solid asphaltenes usually appear brown to black and have no definite melting point but decompose when the temperature exceeds 300-400 o C. It has been shown that changes in temperature [24,25], pressure [26][27][28] and oil composition [29] can cause asphaltene precipitation. Asphaltenes are flat sheets of condensed polyaromatic hydrocarbons interconnected with sulfide, ether, aliphatic chain, and naphthenic ring linkages [30,31].…”
Section: Surface-active Species In Crude Oilmentioning
confidence: 99%
“…The effect of pressure on asphaltene precipitation is generally thought to be reversible [40,74,75], whereas most disagreement is found regarding the influence of temperature and composition. The re-dissolution of precipitated asphaltene at low temperatures is kinetically slow and long periods of time may be required to verify the reversibility of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Apparent irreversibilities have also been associated with inappropriate reversibility criteria [79] and to the existence of an energy barrier to asphaltene dissociation [80]. In spite of the difficulties, the number of studies supporting reversibility is remarkable [74,75,[79][80][81][82][83].…”
Section: Introductionmentioning
confidence: 99%
“…Hirschberg et al 43 assumed that the aggregation was reversible, but probably very slow. Joshi et al 45 found the precipitation from a live crude oil to be reversible in the matter of minutes, except for a subtle irreversibility observed for the first depressurization of the crude oil. They also discussed the different behavior of asphaltenes precipitated from crude oils with excess n-alkanes and by asphaltenes contained in the original crude oil.…”
Section: Solubility and Aggregation Of Asphaltenesmentioning
confidence: 99%
“…Aggregation problems may be encountered both during mixing of crude oils and pressure depletion from reservoir conditions. 45,46 The aggregation and precipitation of asphaltenes may cause a large variety of problems, from formation damage, equipment plugging, catalyst deactivation, etc. In addition, asphaltene aggregation has a great influence on emulsion stability of crude oil-water emulsions.…”
Section: Solubility and Aggregation Of Asphaltenesmentioning
confidence: 99%